Understanding Sharia Governance In Islamic Financial Institution: A Systematic Literature Review And Conceptual Perspective - Khasanah, Uswatun (SHACRAL: Shari'ah Economics Review Journal, 2025)
Sharia governance constitutes a fundamental pillar in ensuring the legitimacy, credibility, and sustainability of Islamic financial institutions (IFIs). Unlike conventional governance frameworks, Sharia governance integrates corporate governance principles with Islamic jurisprudence, aiming to ensure that all financial activities comply with Sharia principles. As the global Islamic finance industry continues to expand, particularly in Muslim-majority countries such as Indonesia, Malaysia, and Gulf Cooperation Council (GCC) states, the effectiveness of Sharia governance practices has become a critical concern for regulators, practitioners, and scholars. This study aims to systematically review and synthesize existing literature on Sharia governance practices in Islamic financial institutions using a qualitative systematic literature review and conceptual approach. The review draws on peer-reviewed international and national journal articles, regulatory documents, and institutional reports published over the last two decades. The analysis focuses on key components of Sharia governance, including the role of Sharia Supervisory Boards (SSBs), internal Sharia audit mechanisms, governance disclosure, and regulatory frameworks established by standard-setting bodies such as the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and the Islamic Financial Services Board (IFSB). The findings indicate that while formal Sharia governance structures have been widely adopted, their implementation varies significantly across jurisdictions due to differences in regulatory enforcement, institutional capacity, and scholarly interpretation of Sharia principles. Empirical evidence from Indonesia demonstrates rapid growth in Islamic financial assets exceeding IDR 1,028 trillion in 2025 yet highlights persistent challenges related to SSB independence, effectiveness, and governance transparency. This study contributes by offering a comprehensive conceptual understanding of Sharia governance practices and identifying key gaps between regulatory expectations and operational realities. The findings are expected to provide insights for policymakers, regulators, and Islamic finance practitioners seeking to strengthen Sharia governance frameworks and enhance institutional accountability.